Le monde de la mort et le monde des blancs - Maranda, Elli Köngäs (Anthropologica, 2022)
This paper presents Lau funeral laments in their recent context of contact with the White world. Analysis of a text shows the kind of stress put on Lau culture in the fringes of urbanization.